Update on the impact of type 2 diabetes mellitus on bone metabolism and material properties - Picke, Ann-Kristin; Campbell, Graeme; Napoli, Nicola; Hofbauer, Lorenz C; Rauner, Martina (Endocrine Connections, 2019)
The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide, especially as a result of our aging society, high caloric intake and sedentary lifestyle. Besides the well-known complications of T2DM on the cardiovascular system, the eyes, kidneys and nerves, bone strength is also impaired in diabetic patients. Patients with T2DM have a 40–70% increased risk for fractures, despite having a normal to increased bone mineral density, suggesting that other factors besides bone quantity must account for increased bone fragility. This review summarizes the current knowledge on the complex effects of T2DM on bone including effects on bone cells, bone material properties and other endocrine systems that subsequently affect bone, discusses the effects of T2DM medications on bone and concludes with a model identifying factors that may contribute to poor bone quality and increased bone fragility in T2DM.